2002
DOI: 10.1034/j.1600-065x.2002.18803.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer/testis antigens: an expanding family of targets for cancer immunotherapy

Abstract: Cancer/testis (CT) antigens are a category of tumor antigens with normal expression restricted to male germ cells in the testis but not in adult somatic tissues. In some cases, CT antigens are also expressed in ovary and in trophoblast. In malignancy, this gene regulation is disrupted, resulting in CT antigen expression in a proportion of tumors of various types. Since their initial identification by T-cell epitope cloning, the list of CT antigens has been greatly expanded through serological expression clonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
616
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 752 publications
(640 citation statements)
references
References 83 publications
(117 reference statements)
13
616
1
5
Order By: Relevance
“…1 Among healthy cells, both are almost exclusively expressed in germ cells at different maturation stages, whereas their expression is detectable in malignancies of different histological origin. Furthermore, both are encoded within chromosome X, albeit in regions distant from each other.…”
Section: Multitissue Array Investigation Of Ny-eso-1/lage-1 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Among healthy cells, both are almost exclusively expressed in germ cells at different maturation stages, whereas their expression is detectable in malignancies of different histological origin. Furthermore, both are encoded within chromosome X, albeit in regions distant from each other.…”
Section: Multitissue Array Investigation Of Ny-eso-1/lage-1 Expressionmentioning
confidence: 99%
“…1 Among C/T antigens, NY-ESO-1 appears to play an important role since it is probably the most immunogenic member of the group and it is also capable to induce humoral responses in addition to specific cytotoxic T lymphocytes (CTL) and CD4þ T cells. 2,3 Remarkably, most recently a highly homologous determinant, LAGE-1, has been reported to be able to induce specific regulatory CD25þ/CD4þ in melanoma tumor infiltrating lymphocytes (TIL).…”
mentioning
confidence: 99%
“…1 Cancer-testis antigens such as NY-ESO-1 have attracted increasing attention as immunotherapeutic targets because, among normal tissues, they are expressed only in adult testis germ cells and are atypically re-expressed in many malignancies. 2,3 NY-ESO-1 is of particular interest to researchers and clinicians because it is highly immunogenic and is expressed in a variety of carcinomas, melanomas, and sarcomas. 4 A recent clinical trial of adoptive immunotherapy, using genetically modified T cells directed against NY-ESO-1, demonstrated objective clinical responses in a number of metastatic synovial sarcoma and melanoma patients with NY-ESO-1-positive tumors.…”
mentioning
confidence: 99%
“…Later, Lewis Thomas has demonstrated that the main cells involved in tumor elimination are cytotoxic T lymphocytes (CTLs). Today's knowledge about the broad spectrum of tumor antigens, recognized by the immune system 6,7 and main principles of immune surveillance, are actively used in development of antitumor immunotherapy. 8 However, a lot of mismatches and contradictions were found in Ehrlich's hypothesis.…”
Section: Modern View On Antitumor Immune Responsementioning
confidence: 99%